A new atyid genus and species from Madagascar (Crustacea: Decapoda: Caridea) - Richard, Jasmine; de Grave, Sammy; Clark, Paul F. (Zootaxa, 2012)
The caridean family Atyidae is currently known by 29 species in Madagascar, which are found throughout riverine habi-tats, caves and swamps. The present study describes a new genus and species from a mountain stream in the RanomafanaNational Park, South East Madagascar. The new genus is characterised by possessing a short unarmed rostrum, absenceof teeth on the carapace, the carpus of the second pereiopod being elongated with an anterior excavation, all pereiopodswith exopods (fifth vestigial or reduced), the presence of a single uropodal diaeresis spine, a long appendix masculinaarmed with numerous spiniform setae on the second male pleopod and in carrying 11–14 eggs of 1.4–1.5 × 1.00–1.1mm in size.